Automated manufacturing processes for secondary structure aerospace composites - Key, Ross A. (2016)
As projected manufacturing rates for commercial aircraft increase to levels of multiple ship sets per day from individual manufacturing facilities, GE Aviation have expressed the need for a shift in composites secondary structure manufacturing philosophy. Traditional manufacturing processes tend to be touch labour intensive and hence costly. The manual placement of large numbers of individual ply profiles, lengthy debulking operations and complex cure cycles, result in excessive component lead times and manufacturing costs. As a result, direct labour cost is a major factor in the total economies of production processes.